Enhancing Community Participation for Sustainable Coastal Empowerment: A Case Study of the Resilient Coastal Area Development Program in Central Java - Waluyo Handoko; Moermahadi Soerjadjanegara; Ida Irawati; Suwarno Suwarno (Research Horizon, 2023)
This study aims to describe the issues and problems related to community participation in the empowerment program entitled the Resilient Coastal Area Development Program (Program Pengembangan Kawasan Pesisir Tangguh or PKPT) in coastal areas. Additionally, it discusses the importance of creating a participatory development model. This study holds significance due to the specific nature of PKPT implementation, which combines a top-down participation mechanism from the central government with a bottom-up approach involving northern coastal communities in Central Java. The research employs a qualitative method, utilizing an action research approach. The study includes informants such as organizers of coastal communities, village heads, village officials, personnel from the Marine and Fisheries Service of Kebumen Regency in Central Java, among others. The results reveal that the PKPT program's implementation in coastal areas of Java, particularly in Kebumen, utilizes both top-down and bottom-up mechanisms, resulting in low community participation in the substantive implementation of PKPT. Consequently, this lack of participation affects the sustainability of the empowerment program. This study presents a participatory development model expected to serve as a reference for organizing sustainable empowerment programs in coastal areas in the future.